Investigation on Phoenix dactylifera/Calotropis procera Fibre-Reinforced Epoxy Hybrid Composites - Mazaherifar, Mohammad Hassan; Hosseinabadi, Hamid Zarea; Coșereanu, Camelia; Cerbu, Camelia; Timar, Maria Cristina; Georgescu, Sergiu Valeriu (MDPI AG, 2022)
This paper presents the investigations conducted on three types of fibre-reinforced epoxy-resin hybrid composites with different structures, manufactured using midrib long fibres of date palm (Phoenix dactylifera L.) and Calotropis procera fibres. The two types of fibres were formed into flat sheets, without adding other chemicals or resins, and employed as reinforcing layers in the structure of the multi-layered laminate composites. Three-layer and five-layer epoxy-reinforced laminates were manufactured from the sheets of date-palm fibres and Calotropis sheets bonded with laminar epoxy resin. Water resistance investigation and mechanical testing under tensile, bending and impact loads were conducted in the research in order to evaluate and compare the performance of the resulting composites. Emphasis was put on the effect of various factors, such as the type of reinforcement material and the number of plies in the laminate on the mechanical behavior of the composites. The interpretation of those results was supported by the stereo-microscopic investigation of the adhesion between the layers of the composites, and the vertical density profile (VDP), which showed the repartition of the density on the composite thickness depending on the layer material. The results of the mechanical performance of the composites showed lower values of tensile strength, tensile modulus of elasticity and impact resistance and an increase of water absorption (WA) and thickness swelling (TS) for the five-layer composites compared to the three-layer composites. Contrarily, the addition of Calotropis fibres improved the flexural strength and the flexural modulus of elasticity. The alkali treatment of the Calotropis fibres improved the mechanical performance of the composites compared to the ones made with untreated fibres, because of an apparent increase in cellulose content and free hydroxyl groups revealed by FTIR spectra.
Keywords: date palm; long fibres; Calotropis fibres; epoxy resin; laminate composites; mechanical testing